Dam failure environmental standards in China based on ecosystem service value - Li, Wei; Yi, Jianni; Liu, Jie; Zhang, Hexiang; Jiao, Yutie (Frontiers in Earth Science, 2023)
Dam failure risk standards are the foundation of risk decision-making for dam managers. However, as an important component of dam failure risk standards, there are currently no unified environmental risk standards. Drawing on research ideas of ecological economics on ecosystem service values and equivalent factor methods, this study quantified environmental values and effectively connected environmental standards with existing standards using the ALARP principle and the F-N curve. Considering the differences in environmental and economic conditions in different regions, a risk preference matrix was constructed to determine the risk preference of each region and formulate the dam failure environmental risk standards for China. This study presents a preliminary exploration of the formulation of dam failure environmental risk standards, providing new methods and ideas for subsequent research.